Dietary intake and obesity in oil and gas workers: A literature review - Nur Lailatuz Zahra; Dian Novita Chandra (Indonesian Nutrition Association, 2021)
Introduction Working in oil and gas industries was found to be associated with unhealthy lifestyle, obesity, and non-communicable diseases (NCDs). This study aimed to systematically review the dietary intake, obesity status, and identify possible workplace health promotion strategies for oil and gas setting. Methods: This literature review was conducted through a comprehensive search of Scopus database. Search terms included diet (and synonym), worker (and synonyms), oil and gas (and synonym). The search was limited to paper in English and Indonesian. Combinations of the keyword yielded 76 papers, of which 13 articles were relevant. Results: Reviewed studies implied that diet consist high amount of fat, particularly saturated fat, and cholesterol, with low intake of dietary fiber. Fatigue, boredom, and inadequate sleep may influence unhealthy food choices. All studies revealed that mean BMI among oil and gas workers was found to be higher than general adult population, ranged from 24 to almost 30 kg/m2. Possible health promotion components to be modified are knowledge and beliefs, self-care, peer support, food availability and time restriction at cafeterias. Conclusion: It is confirmed that obesity and NCDs prevalence were high in oil and gas worker, however the updated studies addressing their dietary intake are needed. Health promotion initiative made by oil and gas company are unlikely to be found in scientific paper. There is a need for more health promotion program that scientifically designed so that the outcome and cost effectiveness can be measured properly